Arah Perubahan Sistem Pemilu Dalam Undang-Undang Politik Pasca Reformasi (Usulan Perubahan Sistem Pemilu Dalam Undang-Undang Politik Pasca Reformasi) - Masyrofah . (Jurnal Cita Hukum, 2013)
The change of Election System in Act related to Politics After Reformation. Elections which were conducted after the reformation: 1999, 2004 and 2009.In order to regulate Election, Act Number 3 Year 1999, Act Number 12 Year 2003 and Act Number 10 Year 2008 were promulgated. There were significant changes in terms of realization of election, election participants, and nomination s of member of House of Regional Representative, House of Representative and House of Council. In addition, there was also substantial change on the 30 percents Quota For Female nominated Member of Parliament.  DOI: 10.15408/jch.v1i2.2988